Audiometric Database of Academic Musicians in Uruguay - Tomasina , Fernando; González, Alice Elizabeth; Pisani Biriel, Myriam Adriana; Tellechea Genta, Bettina; Clavijo , Gimena; Collazo Alza , Gabriela; De Patti, Lorena; Lozano Barra, Beatriz; Palermo, Silvia; Ramirez, Carolina; Schrader, Ulrich (La Medicina del Lavoro, 2025)
Background: This paper presents the results of an interdisciplinary study at the Universidad de la República (Uruguay), in which hearing loss is assessed in a group of academic musicians, including lyric singers, choristers, and orchestral musicians. Methods: Audiometric records from 137 academic musicians were analyzed. The Average Hearing Loss (PAM) methodology, based on Lafon and Duclos combined with the ISO 1999:2013 Standard, was used to convert all the registers to the hearing loss at the age of 35, which were then organized into a permanence curve and compared with reference curves from the ISO 1999:2013 Standard. Results and Conclusion: The results presented here are estimated to represent more than 27 % of the total population of adult academic musicians nationwide. The findings suggest that academic musicians in Uruguay are at a higher risk of noise-induced hearing loss than the general population in the ISO 1999:2013 Standard.